Voluntary Emission Restraints in Developing Economies - Caliendo, Lorenzo,Dolabella, Marcelo,Moreira, Mauricio Mesquita,Murillo, Matthew,Parro, Fernando (National Bureau of Economic Research, 2024)
We study the role of trade policy in one of the most pressing climate policy challenges that developing countries face: meeting voluntary emission restraints (VERs). To do so, we develop a general equilibrium trade model that extends Caliendo and Parro (2015) in three dimensions. First, we model extractive sectors that feature a continuum of producers with heterogeneous productivity, demanding labor, dirty natural resources, and intermediate goods from all industries. Second, we consider that production generates different amounts of emissions across sectors and countries, and households experience disutility from carbon emissions, modeled as a pure externality as in Shapiro (2021). Third, we model a general set of taxes along the value chain–on production, intermediate and final consumption, and on labor–which allows for different options of carbon taxes and tariffs that impact emissions and other outcomes in general equilibrium. In our quantitative analysis, we focus on two groups of policies: those that are in the traditional realm of trade policy, related to tariff reform and potential emission biases; and those that combine a Pigouvian carbon tax with border adjustments. Our main findings point to a nuanced role of trade policy as a climate policy in developing economies. Although it is effective in mitigating emission leakages, such leakages are small in magnitude, and border adjustment tariffs have collateral effects in terms of trade declines, and in many countries, welfare losses. These findings contrast with the implications of climate policy in large economies, where emission leakages are much more significant and the impact on trade less costly. Our main results also indicate that carbon taxes and tariffs will not be enough for most developing countries to meet their net-zero emission targets dictated by the VERs
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Treibhausgas-Emissionen; Selbstverpflichtung; Internationale Klimapolitik; Ökosteuer; Außenwirtschaftspolitik; Internationale Wirtschaft; Entwicklungsländer; General; Trade Policy; International Trade Organizations; Trade and Environment; Economic Impacts of Globalization; Externalities; Redistributive Effects; Environmental Taxes and Subsidies; Environmental Economics; Environment and Development; Environment and Trade; Sustainability; Environmental Accounts and Accounting; Environmental Equity; Population Growth